Leveraging immune checkpoint inhibitors in lung cancer patients with pre-existing autoimmune disease: clinical insights, optimal timing, and predictive biomarkers for optimal treatment outcomes - Yang, Hui; Yu, Sheng; Ge, Hong (Frontiers in Immunology, 2025)
The use of immune checkpoint inhibitors (ICIs) has revolutionized cancer treatment, particularly in lung cancer. However, their use in patients with pre-existing autoimmune diseases (PADs) presents unique challenges. PADs, such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and psoriasis, complicate the clinical management of lung cancer due to concerns about worsening autoimmune symptoms during ICI therapy. This review summarized the safety and efficacy of ICIs in lung cancer patients with PAD, focusing on the available clinical evidence, the optimal timing of ICI initiation, and the potential predictive biomarkers for immune-related adverse events (irAEs). Future prospective studies are needed to establish definitive guidelines for the use of ICIs in this population, with a focus on identifying patients at risk, managing ICI resumption after irAE and developing new medications with durable control of both cancer and PAD.